Risk factors for early mortality and impaired quality of life in oral cavity cancer – head and neck cancer register study - Teija Nieminen; Morag Tolvi; Tuija Ylä-Kotola; Lasse Lehtonen; Antti Mäkitie; Taru Ilmarinen (Acta Oncologica)
Background and purpose: Treatment of locoregionally advanced oral cavity cancer (OCC) is associated with treatment-related complications, functional deficits, and even early mortality. High-quality register data could help in choosing between curative and non-curative intent treatment options.